Analysis of the Role of Financial Technology (Fintech) in Increasing MSME Profits in Medan City - Widya Sirait; Salman Nasution; Asmaul Husna (Journal of Global Islamic Economic Studies, 2023)
This research aims to analyze the role of Financial Technology (Fintech) in increasing the profits of MSMEs in Medan City and analyze the risks and obstacles in using Fintech to increase the profits of MSMEs in Medan City. The method used in this research is descriptive qualitative with the type of data used being primary data and secondary data regarding Fintech, and with descriptive analysis techniques through observations, interviews and documentation. The population used is MSME actors in Medan City and the sample used is 20 MSME actors in Medan City who use Fintech as non-cash payments. The results of this research show that the role of fintech in increasing the profits of MSMEs in Medan City includes: a) providing convenience, speed and comfort for MSMEs in making transactions via digital payments; b) make it easier for MSMEs to manage finances and increase income; c) attract customers and increase sales volume by means of MSME players making promotions via fintech platforms; d) makes it easier for MSMEs to monitor sales and profits because the bookkeeping system is automatic; e) make MSME players more active in innovating to increase types of business and expand their marketing. Meanwhile, the obstacles to using fintech in increasing the profits of MSMEs in Medan City are: a) the use of fintech depends on the internet network, if the network is not good then online payment transactions cannot be used; b) MSME players must pay fees to fintech service providers for their use. Meanwhile, the risks of using fintech to increase MSME profits in Medan City are: a) website disruption caused by hackers.